Fuzzy multi-criteria and multi-experts evaluation of government investments in higher education: the case of Turkey - Kahraman, Cengiz (Technological and Economic Development of Economy, 2013)
Higher education refers to a level of education that is provided at academies, universities, colleges, seminaries, institutes of technology, and certain other collegiate-level institutions. Government investment policy should be concerned with the marginal rate of return when deciding on whether to increase their expenditure on higher education. Government investment in higher education is a decision making problem, which includes multiple and conflicting criteria. We use fuzzy analytic hierarchy process (AHP) to take these criteria into account and to handle vague and incomplete data. We also use fuzzy TOPSIS to compare the results of AHP. A case study for Turkey is realized. In this case study, our multi-criteria decision model evaluates three possible higher education investment alternatives. A sensitivity analysis based on different scenarios of experts’ preferences is also given.